Illegitimate tasks and job satisfaction among employees of micro informal enterprises - Aamar Ilyas; Ramraini Ali Hassan; Ahmed Hussain Khan; Waris Ali Khan (Growing Science, 2020)
This study addresses the illegitimate task-related stressor that establishes a threat to the employees’ self-image. The objective of this study is to provide a clear picture on how illegitimate tasks impact on employees’ mind who work in micro informal enterprises. No single study examined this relationship among employees of informal enterprises. An active employee of micro informal enterprises (MIE’s) within Lahore city is the unit of analysis of this study. The questionnaire of the study was sent to 500 employees of informal enterprises. Participants were 425 full-time employees in informal enterprises at various position levels, representing an 85 percent response rate. SPSS 21 and AMOS 16 statistical packages were used to analyze the collected data. Normality of variables was checked with the help of Skewness and Kurtosis scores. To test the hypotheses of this study, structural equation modeling (SEM) was implemented. The analysis comprises confirmatory factor analysis (CFA) and structural equation modeling (SEM). The findings of this study show that illegitimate tasks also boost the stress level of employees who work in informal entrepreneurship. Consequently, owners and managers of MIE should organize and design such training programs that increase the level of understanding about assigned tasks.